Pengaruh Strategi Pembelajaran dan Motivasi Belajar terhadap Pemahaman Siswa - Sri Agustina Sibuea; Amini Amini; Rizka Ardini; Siti Aminah; Yulita Mailida (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The purposes of this study were to examine the effects of cooperative learning approach of Student Teams-Achievement Divisions (STAD), the level of student’s learning motivation, and the interaction of the two independent variabels to understanding on social studies in elementary student. Cooperative learning was compared to lecture recitation cycle using a quasi- experimental design. An achievement test consisting of items from the state competency test, and a motivation to learn questionnaire adopted from Hari Witono were administered. The analysis of variance(Anova) was used to data analyse. Anova showed a significant difference among the dependent variables from the learning strategies used. There was also a significant difference in student’s understanding on social studies between the high and low levels of motivation to learn. But there was no interaction between the learning strategis and the levels of motivation to learn towards understanding on social studies in elementary school.Based on these findings,it was suggested that teacher need to use cooperative learning type STAD and motivate students to learn, so student’s achievement, especially in social studies subject matter, increased.